ĐẶC ĐIỂM SINH HỌC CỦA XẠ KHUẨN NỘI SINH TRÊN CÂY NGHỆ Ở NAM ĐỊNH VÀ TIỀM NĂNG SINH TỔNG HỢP CHẤT KHÁNG KHUẨN - Đỗ, Tất Thịnh; Ngô, Cao Cường; Vũ, Xuân Nam (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
BIOLOGICAL CHARACTERISTICS OF ENDOPHYTIC ACTINOMYCETES ASSOCIATED FROM CURCUMA LONGA TREES AND THE POTENTIAL TO BIOSYNTHETIZE ANTIMICROBIAL SUBASTANCESEndophytic actinomycetes associated with medicinal plants have widely reported to inhibit microbial pathogens and shown the potential applications. In traditional medicine, Curcuma longa has been used for thousand years. This is a precious medicinal plant, with the desire to find endophytic Actinomycetes strains with many precious properties on medicinal plants. In the paper, roots, branches and leaves of Curcuma longa were collected at Giao Thuy district, Nam Dinh province, Vietnam. The results showed that 8 endophytic Actinomycetes strains were isolated, in which, there are two strains named NVGR3 and NVGC3 could inhibit all tested strains (18.5%) and especially, NVGR3 strain has the best antibacterial activity. The isolated NVGR3 was selected for studying on biological characteristics. This strain reached high biomass yields as grow in several cultivation media at pH 5÷10, salinity up to 7% and growth temperature of 15÷37oC. Based on the results of morphological, physiological and biochemical characterizations and phylogenetic analysis of 16S rDNA, the isolated NVGR3 was identified as Streptomyces collinus species named Streptomyces collinus NVGR3.